2009
DOI: 10.1007/s11255-009-9636-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Charlson’s comorbidity index on overall survival following tumor nephrectomy for renal cell carcinoma

Abstract: There was significant improvement in the quality of life, following tumor nephrectomy, even for Stage-IV cancers. Multivariate analysis indicated besides tumor stage, grade, and size of the tumor, Charlson's index has a significant predictive value on overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Comorbidity, quantified by the Charlson indexwhich includes diabetes-was the most important predictor of hospitalizations in this study. The Charlson index predicts various outcomes in populations with kidney disease [33][34][35] and along with age was found to predict mortality in HD patients [36]. The Charlson score of octogenarians did not differ from that of younger HD patients in this study.…”
Section: Discussionmentioning
confidence: 43%
“…Comorbidity, quantified by the Charlson indexwhich includes diabetes-was the most important predictor of hospitalizations in this study. The Charlson index predicts various outcomes in populations with kidney disease [33][34][35] and along with age was found to predict mortality in HD patients [36]. The Charlson score of octogenarians did not differ from that of younger HD patients in this study.…”
Section: Discussionmentioning
confidence: 43%
“…CCI index is based on 19 categories of comorbidity [3]. Ather and Nazim [14] evaluated the impact of CCI on overall survival following tumor nephrectomy, and identified that CCI had a significant predictive value on overall survival. However, when we searched Medline, we could not reach published data investigating the association between CCI and CPCS in RN cases.…”
Section: Discussionmentioning
confidence: 99%
“…This index was initially validated in a cohort of breast cancer patients [12], giving a method of measuring the prognostic impact of comorbid disease. Since this initial publication, the CCI has been validated and used in several cancer studies, including head and neck [17,18], stomach [19], bladder [20], kidney [21], prostate [22], renal cell carcinoma [23], lung cancer [11,13,24], and cancer in the elderly [25]. In some cancer studies, including head and neck [17], bladder [20], prostate [22], early stage NSCLC [11], the effect of CCI on survival has been proven.…”
Section: Discussionmentioning
confidence: 99%